2021
DOI: 10.21608/tsnj.2021.198905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passage meditation program on nurses' level of hope and resilience who caring for patients with COVID 19

Abstract: Background: COVID-19 is an acute resolved disease but it can also be deadly, with a 2% case fatality rate. Health care workers are the frontline soldiers against COVID-19. They experienced fear, high level of stress, fatigue, grief and anxiety during facing pandemic. So, development and application of a meditative program that consistent with our culture can be valuable to control and overcome stress, building resilience and hope. Aim: To evaluate the effect of passage meditation program on nurses' level of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
1
1
Order By: Relevance
“…This also indicated that the nurses had responded effectively to the intervention program. This point of view was in agreement with some previous studies (Taylor, 2020, Elnehrawy, &Zewiel, 2021 andHarfush et al, 2020). which reported that the mean score of resilience increased post intervention with a highly statistically significant difference between pretest and posttest scores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This also indicated that the nurses had responded effectively to the intervention program. This point of view was in agreement with some previous studies (Taylor, 2020, Elnehrawy, &Zewiel, 2021 andHarfush et al, 2020). which reported that the mean score of resilience increased post intervention with a highly statistically significant difference between pretest and posttest scores.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to some literature, male participants' commitment, control, challenge factor, and total resilience scores did not differ significantly from those of female participants (Elnehrawy, & Zewiel, 2021). Also, (Jose et al, 2020).…”
Section: Discussioncontrasting
confidence: 67%
“…Also, the highest percentage of nursing staff were females, and most nurses in Egypt get married at an early age. This was consistent with the results of previous studies; Keener et al, (2020); Inocian E, et al (2021) (39,40) found that the majority of participants were females, under 25 years of age (Taylor A., 2020) (41) ; and married (Woon et al, 2021) (42) On the contrary, Elnehrawy S. & Zewiel M., (2021), Asnakew et al, 2021) ( (43,44) , mentioned that the majority of nurses were males, single (Jose et al, ( 2020), Elnehrawy S. & Zewiel M., (2021) (45,43) , and the mean age of the respondents was 36.16 (8.17) years or more (Zhang & Ma, 2020) (46) .…”
Section: Discussionsupporting
confidence: 90%
“…Regarding target tradition, most extant adaptation efforts have focused on adapting for adherents to a single tradition (e.g., Christianity or Islam), but a few teach practices that exist in analogous versions across diverse traditions, such as meditating on sacred texts (Oman & Bormann, 2021; see adaptation to Islam by Elnehrawy & Zewiel, 2021), "cultivating spiritual connection" (Feuille & Pargament, 2015, p. 1096, or repetition of a mantram or holy name (Hulett et al, 2023;Oman et al, 2022).…”
Section: Religious Adaptations Of Mindfulnessmentioning
confidence: 99%